KEPUTUSAN INVESTASI PERBANKAN NASIONAL PADA SUKUK INTERNATIONAL ISLAMIC LIQUIDITY MANAGEMENT (IILM) - Nadia Iffatul Ulya; Rifki Ismal2 (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2018)
This study aims to analyze the investment decision of banks and measures their investment preferences in IILM sukuk with IILM sukuk preference index. The investment decision is investigated from several factors, such as the structure of IILM sukuk, the currency used in the transaction IILM sukuk, tenors of IILM sukuk, covenants used in the transaction, marketability of IILM sukuk and IILM sukuk rating. This study also attempts to inform the features that can attract banks to invest in IILM sukuk. This study used quantitative method to calculate the index of banking investment decision on IILM sukuk. The result of this research explains that the index of banking investment decisions includes in the high category. The index investment decisions show a high index, but up to now banks have not invested in IILM sukuk. This needs in-depth education and socialization to banks related to IILM sukuk, and providing periodic information is really essential, so banks can get the latest information about IILM sukuk. Another factor that restricts bank investment in sukuk IILM is internal bank policies. Until now, banks still manage their funds by using investment instruments issued by the state or domestic sukuk. The recommendations for sukuk is related to IILM first appointment of primary dealers, and the institutions are expected to appoint IILM primary dealers located in Indonesia in order to facilitate buying and selling transactions of IILM sukuk. Furthermore, the selection of IILM tenor sukuk is expected to have miraculous tenor selection to meet the needs of banks. Further provision of rating is expected to not only IILM sukuk but also the standardized IILM institution to create more reliable institutions that are able to add the investors.